Ricostruzione policroma - Reboli, Michele (2005)
Sauerbruch Hutton Architects
Keywords: HUTTON, LOUISA; SAUERBRUCH, MATTHÍAS; LUDLOFF, JENS; YOUNG, LUCAS; EDIFICIOS PUBLICOS; COMISARÍAS; CUARTELES DE BOMBEROS; AMPLIACION; FACHADAS; VIDRIO